Insights and learnings from lean manufacturing implementation practices. (6th May 2010) - Yadav, Om Prakash; Nepal, Bimal; Goel, Parveen S.; Jain, Rakesh; , R.P. Mohanty
Lean manufacturing as a set of principles is now fairly rooted in the literature. Barring some voices of discontent (Gordon, 1995; Berggren, 1992) regarding the adoption and ultimate effectiveness of lean production, many case examples exist to demonstrate how companies are changing their production methods and management practices to become more lean and fit. The main aim of this study is to first collect information on fundamental lean principles and then investigate the level of lean implementation in the automotive industry. Furthermore, it describes some learnings from actual implementation practices particularly in the USA, UK and Indian automotive sectors. Attempts are made here to discover the inside stories and present the gaps between the principles and actual practices.